Contributions to inclusive economic growth in Argentina: integrating design, marketing and entrepreneurship for local development in Buenos Aires Province - Del Giorgio Solfa, Federico (2015)
This work aims to study strategies used in Argentine local development experiences, focusing on industrial design, marketing and entrepreneurship. In order to this purpose, we analyse backgrounds with this approach adding the study of three strategic plans for national and provincial level that are currently in force. With the analysis of the transport system in the last decade, an accelerated cost increase is evident, resulting in a relatively higher price of distributed products. This situation that was initially perceived as a disadvantage finally set up an opportunity to produce locally. The goal of this paper is to provide tools that contribute to the work shipped by key institutions for local development (public, private and intermediary organizations); and the way these interact with the actors and the territory. In particular, the identification of productive sectors and the selection of goods that can be produced and consumed locally, as a key input for the formulation of projects.